2009
DOI: 10.1007/s12602-009-9021-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mode-of-Action of the Two-Peptide (Class-IIb) Bacteriocins

Abstract: This review focuses on the structure and mode-of-action of the two-peptide (class-IIb) bacteriocins that consist of two different peptides whose genes are next to each other in the same operon. Optimal antibacterial activity requires the presence of both peptides in about equal amounts. The two peptides are synthesized as preforms that contain a 15–30 residue double-glycine-type N-terminal leader sequence that is cleaved off at the C-terminal side of two glycine residues by a dedicated ABC-transporter that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 68 publications
(146 reference statements)
1
146
0
1
Order By: Relevance
“…It has been suggested that most two-peptide bacteriocins probably form a transmembrane helix-helix structure (11). In the case of the two-peptide bacteriocin lactococcin G, one of the peptides (LcnG-␣), like LsbB, contains a series of cationic residues (residues 35-39: RKKKH) at the C-terminal part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that most two-peptide bacteriocins probably form a transmembrane helix-helix structure (11). In the case of the two-peptide bacteriocin lactococcin G, one of the peptides (LcnG-␣), like LsbB, contains a series of cationic residues (residues 35-39: RKKKH) at the C-terminal part.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structures of only a few bacteriocins have presently been determined; these mostly include some modified bacteriocins called lantibiotics and some nonmodified bacteriocins belonging to the pediocin-like and two-peptide bacteriocin subgroups (7)(8)(9)(10)(11). Even for these bacteriocins, very little is known about the part of these peptides that is directly involved in receptor binding or pore formation (12).…”
mentioning
confidence: 99%
“…Наслідком зв'язування бактеріоцину з рецептором є перетворення комплексу «бактеріо-цин-транспортер» на трансмембранний канал, через який відбувається витік розчинних компонентів цитоплазми. Білок, що забезпечує автоімунітет до педіоцин-подібних бактеріоцинів, не секретується назовні, а є цитоплазма-тичним комплексом, пошкождує мембрану, зв'язуючись з ним з цитоплазма-тичного боку [52].…”
Section: в немодифіковані бактеріоциниunclassified
“…This group is oftentimes called pediocin-like because the first discovered bacteriocin belonging to this group was pediocin PA-1/AcH Drider et al 2006). While class IIb bacteriocins are twopeptide bacteriocins that require both peptides to work synergistically to be fully active (Oppegard et al 2007;Nissen-Meyer et al 2010), class IIc bacteriocins, arguably the most poorly understood, are grouped based on the circular configuration of their structure. The N-and C-termini of class IIc bacteriocins are covalently linked that results to a very stable molecular structure (Maqueda et al 2008;van Belkum et al 2011).…”
Section: Lab Bacteriocin Classificationmentioning
confidence: 99%